IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN PAI SMP NEGERI 1 BARUSJAHE - Uni Sahara Br Barus (CV. Arsy Persada Quality, 2025)
This research aims to improve learning outcomes in PAI subjects for Class VIISMP Negeri 1 Barusjahe students by using the jigsaw type cooperative learning model. This research uses classroom action research methods. This research uses a qualitative approach. The subjects in this classroom action research consisted of Class VII Even Semester students at SMP Negeri 1 Barusjahe, in the Islamic Religious Education (PAI) subject. Data collection techniques use observation, interviews and test results. Data analysis uses data reduction, data presentation, and drawing conclusions. The learning outcomes of students who use the cooperative learning model, after being given the first cycle learning actions (cycle I), the average score of student learning evaluation results is 66.67% and is classified as still below the existing ideal score, namely 75%. Meanwhile, in the implementation of cycle II, 86.67% of students obtained scores that reached the KKM from the final evaluation results given. Thus, learning outcomes using the jigsaw type cooperative model in PAI lessons at SMP Negeri 1 Barusjahe are said to be very good and have experienced significant improvement.